2010
DOI: 10.1002/ajim.20858
|View full text |Cite
|
Sign up to set email alerts
|

Industry‐wide medical surveillance of California flavor manufacturing workers: Cross‐sectional results

Abstract: The flavoring industry risk of severe lung disease justifies lowering flavoring exposures and medical screening for secondary prevention until worker safety is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 8 publications
0
39
0
Order By: Relevance
“…26 Finally, a cross-sectional analysis of medical surveillance data from 16 companies confirmed the risk of lung disease among workers at companies using diacetyl. 27 AP is chemically and structurally almost identical to DA, has a similar buttery, creamy flavor, and has been used as a DA substitute in many flavoring manufacturing facilities. 14 Toxicological studies in animals have shown that it has adverse effects on respiratory epithelium similar to DA and at similar levels.…”
Section: Toxicity Of Da and Apmentioning
confidence: 99%
“…26 Finally, a cross-sectional analysis of medical surveillance data from 16 companies confirmed the risk of lung disease among workers at companies using diacetyl. 27 AP is chemically and structurally almost identical to DA, has a similar buttery, creamy flavor, and has been used as a DA substitute in many flavoring manufacturing facilities. 14 Toxicological studies in animals have shown that it has adverse effects on respiratory epithelium similar to DA and at similar levels.…”
Section: Toxicity Of Da and Apmentioning
confidence: 99%
“…Restriction has also been noted in other microwave popcorn plants [NIOSH 2003]. In flavoring manufacturing employees in California, there were more employees with restrictive than with obstructive spirometric abnormalities [Kim et al 2010]. One case report documents restrictive spirometry in a food production plant worker who used flavorings.…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients with obliterative bronchiolitis on lung biopsy have been found to have normal or restrictive spirometry and normal diffusing capacity [King et al 2011]. Prior evaluations at other flavoring manufacturing facilities have documented a variety of lung function abnormalities, including obstruction [Kim et al 2010], restriction [NIOSH 2011b], and increased declines in lung function over time . In addition, given the diversity of potential exposures in the facility, we considered the possibility that other adverse health outcomes involving the respiratory tract, mucous membranes, and skin were possible.…”
Section: Discussionmentioning
confidence: 99%